ChemInform Abstract: Chiral γ‐Lactams by Enantioselective Palladium(0)‐Catalyzed Cyclopropane Functionalizations. Issue 5 (January 2016) - Pedroni, Julia; Cramer, Nicolai
Abstract: Enantioselective Pd(0)‐catalyzed cyclization of N‐chloroacetyl substituted cyclopropylamines (I) and (III) offers a novel approach to cyclopropane fused chiral bicyclic pyrrolidines (II) and (IV) with moderate to good stereoselectivity.